2011
DOI: 10.1371/journal.pone.0023473
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Replication of over 180 Genetic Associations with Self-Reported Medical Data

Abstract: While the cost and speed of generating genomic data have come down dramatically in recent years, the slow pace of collecting medical data for large cohorts continues to hamper genetic research. Here we evaluate a novel online framework for obtaining large amounts of medical information from a recontactable cohort by assessing our ability to replicate genetic associations using these data. Using web-based questionnaires, we gathered self-reported data on 50 medical phenotypes from a generally unselected cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(110 citation statements)
references
References 42 publications
5
105
0
Order By: Relevance
“…Longitudinal survey data suggest that awareness and understanding may be increasing (Miller, 2004;Singer et al, 2008). The increased participation of the public in personal genomics activities, including research and direct-toconsumer genomic services (Eriksson et al, 2010;Do et al, 2011;Tung et al, 2011) may be due, in part, to the public's increased awareness and understanding of genetics.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal survey data suggest that awareness and understanding may be increasing (Miller, 2004;Singer et al, 2008). The increased participation of the public in personal genomics activities, including research and direct-toconsumer genomic services (Eriksson et al, 2010;Do et al, 2011;Tung et al, 2011) may be due, in part, to the public's increased awareness and understanding of genetics.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the expense of meticulous phenotyping is too great, greater power can be achieved by accepting a small error rate in much larger samples obtained with cheaper, minimal phenotyping. For example, using online questionnaires, a recent genetic study replicated hundreds of previously reported GWAS loci that were originally identified by studies using stricter measures (Tung et al, 2011). Thus, answers to 'Have you ever been diagnosed by a doctor with high cholesterol (over 200 mg/dl) or hypercholesterolemia?'…”
Section: Large-scale Clinical and Genetic Studiesmentioning
confidence: 82%
“…Data being gathered by 23andMe shows a tremendous concordance between self-reported and clinically reported health information. 95 …”
Section: Validation Of Participant Populationmentioning
confidence: 99%